Learning to teach history in the secondary school a companion to school experience - Haydn, Terry 1951-; Stephen, Alison (Routledge, Taylor & Francis Group, 2022)
"In some hands, history can be an inspirational and rewarding subject, yet in others it can seem dry and of little relevance. Learning to Teach History in the Secondary School, now in its fifth edition and established as one of the leading texts for all history student teachers enables you to learn to teach history in a way that pupils will find interesting, enjoyable and purposeful. It incorporates a wide range of ideas about the teaching of history with practical suggestions for classroom practice. The fifth edition has been thoroughly updated in the light of recent developments in the field of history education. The book contains chapters on: Purposes and benefits of school history Planning strategies Teaching approaches and methods Developing pupils' historical understanding Ensuring inclusion New technologies in the history classroom Assessment and examinations Your own continuing professional development Each chapter includes suggestions for further reading, weblinks to useful resources and a range of tasks enabling you to put learning into practice in the classroom. Written by experts in the field, Learning to Teach History in the Secondary School offers all training and newly qualified teachers comprehensive and accessible guidance to support the journey towards becoming an inspirational and engaging history teacher"--